High neuronatin (NNAT) expression is associated with poor outcome in breast cancer - Naß, Norbert; Sel, Saadettin (Virchows Archiv, 2017)
Neuronatin (NNAT) is a proteolipid involved in cation homeostasis especially in the developing brain. Its expression has been associated with the progression of lung cancer, glioblastoma, and neuroblastoma as well as glucose induced apoptosis in pancreatic cells. We performed a retrospective study of 148 breast cancer specimens for NNAT expression by immunohistochemistry to evaluate this protein as a prognostic marker for breast cancer. We found a high NNAT immunoreactivity score (by multivariate cox regression) to be an independent prognostic marker for relapse-free (hazard ratio HR = 3.55, p = 0.002) and overall survival (HR = 6.29, p < 0.001). However, NNAT expression was not associated with classical parameters such as hormone receptor expression (p = 0.86) or lymph node metastasis (p = 0.83). Additional independent risk factors in this study population were tumor size (≤2 cm; overall survival: HR = 0.36, p = 0.023; relapse-free survival: HR = 0.26, p < 0.01) and blood vessel infiltration (overall survival: HR = 0.34 p < 0.01). NNAT expression determined by immunohistochemistry might therefore become a helpful additional biomarker to identify high-risk breast cancer patients.